1998
DOI: 10.1143/jjap.37.l1540
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Defect Control in GaN Using Low Temperature Interlayers

Abstract: In organometallic vapor phase epitaxial growth of GaN on sapphire, the role of the lowtemperature-deposited interlayers inserted between high-temperature-grown GaN layers was investigated by in situ stress measurement, X-ray diffraction, and transmission electron microscopy. Insertion of a series of low temperature GaN interlayers reduces the density of threading dislocations while simultaneously increasing the tensile stress during growth, ultimately resulting in cracking of the GaN film. Low temperature AIN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
87
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(92 citation statements)
references
References 18 publications
4
87
0
1
Order By: Relevance
“…Recently, we found that the insertion of a low-temperature-deposited interlayer between high-temperature-grown GaN layers significantly reduces the density of threading dislocations in the upper GaN layer [9,10]. In this paper, details of the process of lowtemperature interlayers are shown.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, we found that the insertion of a low-temperature-deposited interlayer between high-temperature-grown GaN layers significantly reduces the density of threading dislocations in the upper GaN layer [9,10]. In this paper, details of the process of lowtemperature interlayers are shown.…”
Section: Introductionmentioning
confidence: 92%
“…With the increasing growth temperature of the interlayer, it can further reduce the composition pulling effect. 4 This implies that the insertion of a high-temperature grown interlayer could generate more tensile strain, 15 which in turn compensates for the compressive strain induced by the incorporation of indium in the QWs.…”
mentioning
confidence: 99%
“…Another way to reducing leakage current is fabricating PDs by the epitaxial lateral overgrown technique [9], but it requires a relatively complicated procedure. Recently, the use of low-temperature (LT)-AlN interlayer between two high-temperature epitaxial layers to reduce threading dislocations and control stress in III-nitride epitaxial system has been reported [10], [11]. Compared to the LT-AlN interlayer, the high-temperature AlN interlayer will induce higher dislocation density in the subsequently grown epitaxial layers [12].…”
mentioning
confidence: 99%
“…It should be noted that the dark current of the PD with an LT-AlN interlayer was over two orders of magnitude lower than that of the conventional PD at the reverse bias of 40 V. The origin of high dark current in conventional PD is attributed to the leakage current paths formation from the threading dislocations and related defects. It has been reported that threading dislocations can be suppressed from extending to the following high-temperature epitaxial layers (top p-GaN and upper i-GaN layers) by inserting an LT interlayer [10], [11]. Amano et al showed that both LT-AlN and LT-GaN interlayers can reduce the dislocation density of GaN layers by about one order of magnitude [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation